2009
DOI: 10.1016/j.jenvman.2009.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Using secondary data to analyse socio-economic impacts of water management actions

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Censuses have traditionally been a key source of localised information on the state of a nation's health [26] . Composite measures of socioeconomic deprivation are often used to capture the burden of socioeconomic adversity experienced by a neighborhood [27] . By drawing on a range of indicators, the IMD is considered to more precisely reflect the complex and multifactorial concept of area level deprivation.…”
Section: Datamentioning
confidence: 99%
“…Censuses have traditionally been a key source of localised information on the state of a nation's health [26] . Composite measures of socioeconomic deprivation are often used to capture the burden of socioeconomic adversity experienced by a neighborhood [27] . By drawing on a range of indicators, the IMD is considered to more precisely reflect the complex and multifactorial concept of area level deprivation.…”
Section: Datamentioning
confidence: 99%
“…Whilst the ecological validity and success of river restoration remain contentious (e.g. Kondolf, 2006;Montgomery, 2008;Palmer, et al 2010), there is also particular concern that the social dimensions of the river restoration process are neglected (Åberg and Tapsell, 2013;Buijs, 2009;Junker et al, 2007;Selman et al, 2010;Westling et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As Westling et al . () note, however, there is little evidence that multiple benefits are realized from restoration projects. Our findings provide specific support for previous work suggesting a lack of coordination among researchers and funders or their contractors in planning, implementing, or monitoring stream restoration projects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that restoration projects are often site-specific, small-scale, and opportunistic (i.e., they occur when funding, land, and landowner support are present) rather than implemented as part of a broader effort to address watershed scale land and water use impacts Wohl et al, 2005;Alexander and Allan, 2007;Christian-Smith and Merenlender, 2010). Additional studies focus on the importance of aesthetics in restoration activities and that aesthetic values and ecological values sometimes align and sometimes do not (Larned et al, 2006;Gobster et al, 2007;Chin et al, 2008;Junker and Buchecker, 2008;Westling et al, 2009;Wyzga et al, 2009). Finally, there is strong evidence that practitioners do not seek information from the academic literature and that there is a general lack of communication between researchers and those who implement restoration projects (Rhoads et al, 1999;Wohl et al, 2005;Wheaton et al, 2006;Bernhardt et al, 2007;O'Donnell and Galat, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation